2019
DOI: 10.1186/s12866-018-1383-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergy of sertraline and tetracycline cannot be reproduced in pigs orally challenged with a tetracycline resistant Escherichia coli

Abstract: BackgroundAntimicrobial helper-compounds may reverse antimicrobial resistance. Sertraline, a antidepressant drug, has been suggested as a tetracycline helper-compound. Tetracycline is the preferred antimicrobial for treatment of enteric diseases in pigs. This study is the first to evaluate the potency of sertraline as a tetracycline adjuvant in pigs.MethodsForty-eight nursery pigs were divided into four treatment groups: Tetracycline, sertraline, tetracycline/sertraline or un-medicated control. Fecal and ileal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Consequently, the lowest concentration which inhibits the growth of both Escherichia coli and Enterococcus faecalis was determined as 37.5 µg/ml. Our study was correlated with previous report in which sertraline showed antibacterial effect against Escherichia coli in combination with tetracycline [Kromann S et al, 2019]. Our study was supported by previous study wherein a repurposing ebselen (organoselenium compound) showed excellent activity against both methicillin and vancomycin resistant Staphylococcus aureus by inhibiting the protein synthesis and toxin production [Thangamani S et al, 2015].…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, the lowest concentration which inhibits the growth of both Escherichia coli and Enterococcus faecalis was determined as 37.5 µg/ml. Our study was correlated with previous report in which sertraline showed antibacterial effect against Escherichia coli in combination with tetracycline [Kromann S et al, 2019]. Our study was supported by previous study wherein a repurposing ebselen (organoselenium compound) showed excellent activity against both methicillin and vancomycin resistant Staphylococcus aureus by inhibiting the protein synthesis and toxin production [Thangamani S et al, 2015].…”
Section: Discussionsupporting
confidence: 91%
“…For minocycline, about 19-35% of the dose could be found unchanged in feces after administration to patients (Macdonald et al, 1973;Jonas and Cunha, 1982). As a consequence of intestinal elimination, tetracyclines given by oral or parenteral route modify the gut microbiota (as demonstrated in vitro in human microbiota and in vivo in pigs) (Wagner et al, 2008;Graesbøll et al, 2017;Keerthisinghe et al, 2019;Kromann et al, 2019) and amplify tetracycline-resistant coliform bacteria (Graesbøll et al, 2017;Kromann et al, 2019). Nonetheless, clinical studies of the effects of therapeutic doses on the patients' microbiota remain relatively scarce (Sullivan et al, 2001;Ley et al, 2006), whereas exploring the link between therapeutic doses and gut exposure to active drug, in terms of time development and magnitude, is essential for understanding the emergence and spread of MDR bacteria inside the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%